Origin and evolution of the Italian subterranean termite Reticulitermes lucifugus (Blattodea, Termitoidae, Rhinotermitidae). Issue 6 (24th July 2013) - Luchetti, A.; Scicchitano, V.; Mantovani, B.
Abstract: The Holarctic genus Reticulitermes shows seven species within the Mediterranean Basin. While phylogeny and systematics at continental level has been deeply investigated, a few studies concentrated on local ranges. To gain a clearer picture of the diversity and evolution of the Italian species Reticulitermes lucifugus, we analyzed the mitochondrial cytochrome oxidase II (COII) gene marker in newly collected colonies across the Peninsula. Data were gathered with all R. lucifugus sequences available from previous studies; COII sequences of the closely related Iberian taxa were also added to the data set. Maximum-likelihood, median-joining and statistical parsimony network elaborations on the resulting 119 colonies all agreed in indicating that: (i) the Sardo-Corsican subspecies R. lucifugus corsicus, strictly related to Southern Italian populations (including the Sicilian ones), is phylogenetically closer to the Iberian Reticulitermes grassei ; and (ii) R. lucifugus lucifugus peninsular populations are structured into three clusters. The phylogenetic relationships and the biogeography of extant taxa suggest a scenario in which R. lucifugus ancestors colonized the Italian region through the Sardo-Corsican microplate during its Oligocene-Miocene anticlockwise rotation. Moreover, well after the colonization took place, northward range expansion might have produced the presently observed genetic diversity, as inferred from haplotype and nucleotide diversity estimates. On the whole, this study highlights the evolution of Italian Reticulitermes taxa and supports the importance of a wide taxon sampling especially when dealing with organisms easily dispersed by human activities.